Espiritualidade, florescimento, vínculos organizacionais e desempenho no trabalho: estudo em uma cooperativa de crédito - Kuhn, Nuvea (2024)
In recent years, research has been conducted to deepen the understanding of the factors that influence work behavior and organizational dynamics. Thus, the main objective of this thesis is to analyze the relationships between spirituality, flourishing, organizational bonds, and job performance, from the perspective of workers at a Brazilian credit union. The Systematic Literature Review (SLR) on the panorama of studies that related spirituality and job performance initially identified the main gaps and novelties in relation to the topic. The empirical results were organized into six studies aligned with the established objectives. As methodological procedures, an applied, quantitative, cross-sectional, exploratory, descriptive, correlational, and explanatory research was carried out. The data were collected between October 2022 and May 2023, and the analyses were developed with the aid of the Statistical Software PacKage for Social Science (SPSS) version 26 and SmartPLS® version 4.1.0.2. The research involved a total of 702 workers, the majority of whom were women (54.1%), with specialization (56.6%) and with 1 to 2 years (36.2%) in the credit union. Among the main results, a high level of spirituality, flourishing, commitment and job performance was noted. In terms of relationships between the constructs, Article 1 demonstrates that spirituality has a statistically significant and direct relationship with organizational commitment and consent, and an inverse relationship with the limitation of alternatives (organizational entrenchment). Article 2 identifies the influence of individual flourishing at work in relation to organizational ties (organizational commitment, entrenchment and consent). Article 3 highlights a statistically significant and direct relationship between commitment, organizational consent and job performance. In addition, Article 4 highlights the relationship between the dimensions of spirituality and job performance. In terms of mediation, Article 5 demonstrates that spirituality influences job performance through organizational commitment. Finally, Article 6 shows the influence of spirituality on job performance, through individual flourishing and organizational commitment. As conclusions, the results suggest that spirituality has a positive effect on organizational commitment, individual flourishing and job performance, promoting a more human and sustainable approach for the credit union.